Acts of memory : cultural recall in the present - Bal, Mieke; Crewe, Jonathan V.; Spitzer, Leo (Hanover, NH : Dartmouth College : University Press of New England, 1999)
Acts of Memory presents 15 tightly integrated essays that illustrate the active role of individual and cultural memory in tying the past to the present. Memory, or memorialization, is a cultural activity occurring in the present that offers history another kind of source or document; one that provides insights into the past as it lives on today. The authors, in fields ranging from philosophy and history through literature and media studies, illustrate how memory serves many purposes, between conscious recall and unreflected re-emergence, between nostalgic longing for what is lost to polemical use of the past to reshape the present. Their essays coalesce around three topics: the need for memory and testimonial facilitation of memory, primarily in the case of historical and individual trauma; the site-specific nature of acts of memory, especially in geopolitically conflicted situations; and the potential contributions of acts of memory when facing the difficulties and needs of the present. "Neither remnant, document, nor relic of the past, nor floating in a present cut off from the past, cultural memory, for better or worse, binds the past to the present and future. It is that process of binding that we explore in this volume" writes Mieke Bal.

CONTRIBUTORS: Carol B. Bardenstein, Susan J. Brison, Ann Burlein, Katharine Conley, Lessie Jo Frazier, Gerd Gemünden, Marianne Hirsch, Andreas Huyssen, Irene Kacandes, Mary Kelley, Marita Sturken, Ernst van Alphen, and the editors
Bibliografija uz pojedina poglavlja
Keywords: kultura; povijest; sjećanje; kulturalni studiji; engleska književnost; književna kritika